A study on the application of different lowland and intermediate upland soil types found in Davao City for interlocking compressed earth blocks (ICEBs) - Biala, Christine Joyce G. (2016)
Over the last fifty years, Interlocking Compressed Earth Block (ICEB) technology has been known to be an alternative building construction material for accessible high-quality low cost housing. However, earth building construction using limesoil in Davao City was found to be unsustainable since sources of limesoil are few and far between resulting to increased cost and production time. Several studies examind the nature of ICEB and established different conclusions into production manuals, which serve a lead into provision of manuals on ICEB construction and design. A few studies conducted experiments determining material properties of ICEBs with particular sil textures and different cement ratios. This study examined seven out of twelve particular soil types within Davao City, Phlippines as a possible source of earth component in ICEB production; all of which belong to six soil series namely; Cabantian soil series, San Manuel soil series, Matina soil series, Tugbok soil series, Faraon soil series and San Miguel soil series. Samples of seven soil types were mixed with three different cement ratios to produce ICEBs. These cement ratios are 1:8(12.5%), 1:12 (8:33%) and 1:16 (6.25%). There were n=3 blocks produced per soil type per cement ratio, for a total of 63 samples for the seven different soil types. These samples were observed and assessed based on appearance, texture, dimensions, shape, and shrinkage. Experimentations on the ICEB samples were conducted through test on dry compressive strength and water absorption. Results on dry compressive strength showed that ICEBs with higher cement content had better performance. Higher densities and sand distribution contributed to favorable dry compressive strengths per cement ratio. Moreover, results on water absorption showed that ICEBs with higher clay content and less cement content performed better, as well as ICEBs with higher sand and cement content. In conclusion, higher cement content yielded higher compressive strength and more water absorbed, while higher sand content resulted to higher density of ICEBs and increased compressive strength. Improvement on ICEB design as well as research on its material properties are recommended through investigation on stabilizers, studies on other soil textures, and further analysis on clay particles.